Search for new physics in same-sign dilepton events in proton-proton collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2016)
A search for new physics is performed using events with two isolated same-sign leptons, two or more jets, and missing transverse momentum. The results are based on a sample of proton-proton collisions at a center-of-mass energy of 13[Formula: see text] recorded with the CMS detector at the LHC, corresponding to an integrated luminosity of 2.3 [Formula: see text]. Multiple search regions are defined by classifying events in terms of missing transverse momentum, the scalar sum of jet transverse momenta, the transverse mass associated with a [Formula: see text] boson candidate, the number of jets, the number of [Formula: see text] quark jets, and the transverse momenta of the leptons in the event. The analysis is sensitive to a wide variety of possible signals beyond the standard model. No excess above the standard model background expectation is observed. Constraints are set on various supersymmetric models, with gluinos and bottom squarks excluded for masses up to 1300 and 680[Formula: see text], respectively, at the 95 % confidence level. Upper limits on the cross sections for the production of two top quark-antiquark pairs (119[Formula: see text]) and two same-sign top quarks (1.7[Formula: see text]) are also obtained. Selection efficiencies and model independent limits are provided to allow further interpretations of the results.